(untitled) (SAARC Journal of Agriculture, 2018)
Development of broodstock of the green mud crab (Scylla paramamosain) was assessed under three different captive growout protocols viz. in the open fibre glass tanks (T1), in plastic boxes (T2) floating on fibre glass tanks and in plastic drawer/compartment (T3) for a period of 5 months under the Centre for Marine and Coastal Studies (CEMACS), Universitiy Sains Malaysia (USM). The male (M) and female (F) mud crab were cultured separately to maintain virginity. Suitability of both the sexes were evaluated considering the weight gain (size), survival and intactness of limbs during harvesting. Result of the present study revealed that, irrespectives of growout protocols, growth of mud crab happened following the sigmoid pattern. A noticeable intersexual weight attainment was observed with significantlyhigher (p<0.05) weight gain for the males. Meanwhile, growth was influenced by the culture protocols for both the sexes with significant (p<0.05) weight gain in outdoor tanks (M= 319.75 g, F= 246.17 g) followed by outdoor floating boxes (M= 250.50 g, F= 198.70 g) and indoor compartment (M= 246.40 g, F= 178.50 g). Survival and the proportion of intact crabs under indoor compartment and outdoor floating boxeswere significantly higher (p<0.05) than out door tank culture system. The result of the present study suggested that, outdoor growout protocol could be followed for faster broodstock development purposes to reduce the dependence on natural broodstock for hatchery operations. SAARC J. Agri., 16(1): 169-180 (2018)